Analysis and construction status of SG-II 5PW laser facility. (1st June 2018) - Zhu, Jianqiang; Xie, Xinglong; Sun, Meizhi; Kang, Jun; Yang, Qingwei; Guo, Ailin; Zhu, Haidong; Zhu, Ping; Gao, Qi; Liang, Xiao; Cui, Ziruo; Yang, Shunhua; et al.
Abstract : We present a recent progress of the SG-II 5PW facility, which designed a multi-petawatt ultrashort pulse laser based on optical parametric chirped-pulse amplification (OPCPA). The prior two optical parametric amplifiers have been accomplished and chirped pulses with an energy of 49.7 J and a full-width-at-half-maximum (FWHM) spectrum bandwidth of 85 nm have been achieved. In the PW-scale optical parametric amplification (OPA), with the pump pulse that has an energy of 118 J from the second harmonic generation of the SG-II 7th beam, the pump-to-signal conversion efficiency is up to 41.9%, which to the best of our knowledge is the highest among all of the reported values for OPCPA systems. The compressed pulse is higher than 37 J in 21 fs (1.76 PW), and the focal spot is 10 [STIX]x03BCm after the closed-loop corrections by the adaptive optics. Limited by the repetition of the pump laser, the SG-II 5PW facility operates one shot per hour. It has successfully been employed for high energy physics experiments.